Facilitators and barriers to the uptake of COVID-19 vaccine precaution dose among adult population: qualitative analysis across six different states of India - Godbole, Sheela; Diwan, Vishal; Das, Saibal; Reddy, Mahendra M.; Kalyanasundaram, Madhanraj; Rajendran, Dilipkumar; Biswas, Dipankar; Mamulwar, Megha; Tiwari, Rajnarayan R.; Majumder, Joydeep; Mishra, Ayush; Muthusamy, Santhosh Kumar; et al. (Frontiers in Public Health, 2024)
Introduction India launched the COVID-19 vaccination drive on 16th January 2021 by vaccinating the adult population above 18 years of age. This was followed by the introduction of an additional precaution dose. As on 18th October 2022, 1,02,66,96,808 (1.02 Billion) first dose and 94, 95, 39,516 (949 Million) second doses of COVID-19 vaccine were administered. However, when compared to the uptake of the primary doses, the precaution dose uptake lagged behind with only 21,75, 12,721 (217 million) doses administered. Even though, the uptake of the primary doses remained optimal, irrespective of different interventions by the Government of India, the uptake of the precaution dose remained poor. In this context, the Ministry of Health & Family Welfare wanted to understand the facilitators and Barriers for precaution dose uptake among adults so that future immunization campaigns could address these issues. Methods An exploratory qualitative study was conducted to assess the facilitators and barriers for COVID-19 precaution dose uptake at community level across 6 different states in India. From each of the states, two districts with the highest and lowest rates of COVID-19 vaccine precaution dose uptake were selected. In each of these districts, 2 block Primary Healthcare Centres (PHCs), one with high and one with low uptake were identified. Within these block PHCs, a PHC field area with high and low precaution dose uptakes was identified. From the identified sites a minimum of four IDIs, four FGDs were conducted among the community members. KIIs of the State Immunization Officers, District Immunisation Officers, PHC Medical Officers, healthcare workers like Accredited Social Health Activist/Auxiliary Nurse Midwife were also conducted. The data was audio recorded and it was transcribed, translated and analysed using framework approach. Results It was observed that rise in COVID-19 cases prompted the community to take the precaution dose, this along with the cost of hospitalization and the number of productive days being lost as a result of being infected resulted in vaccine uptake. The fear of non-availability of COVID-19 vaccines latter on also prompted people for vaccine uptake. While the barriers were, poor accessibility to vaccination centers, long hours of travel, poor road connectivity and lack of transportation facilities. However, the most prominent barriers observed across all study sites was that a sense of pandemic fatigue and complacency had developed both among the providers as well as the beneficiaries. Other barriers include differences in vaccination schedules and longer duration between the primary doses of some vaccines. Media was identified to be both a barrier and facilitator for Covid-19 Precaution dose uptake. Even though media played an important role in disseminating information in the beginning of the campaign, it was soon followed by the circulation of both misinformation and disinformation. Discussion The study identified that dissemination of accurate information and community involvement at each stage of planning and implementation are crucial for the success of any campaign. Efforts should be constantly made to address and re-invent strategies that will be most suitable for the needs of the community. Therefore, in order to ensure successful vaccination campaigns, it is crucial that along with political will it is also important to have a decentralized approach with inter-sectoral coordination with different stakeholders such as healthcare workers, community members and the different departments such as the local self-governments, education department, law & order department etc. These lessons learnt from COVID-19 vaccination campaigns must not be forgotten and must be applied in future vaccination campaigns and while framing public health policies.